Penguatan Kapasitas Digital UMKM Desa Wisata Melalui Pelatihan Digital Marketing di Desa Cipada, Bandung Barat - Disya Shafa Azizah; Andi Suwandi; Falah Muhammad Abdan Syaqura; Pauzy Try Suryadi; Zulfa Faadyah; Sukmadi; Wawan Gunawan (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
Tourism villages are a strategic instrument for equitable economic development in Indonesia, yet many, including Cipada Tourism Village in West Bandung Regency, remain constrained by limited digital literacy and the absence of an integrated digital marketing ecosystem. This community service activity aimed to strengthen the digital capacity of micro, small, and medium enterprises (MSMEs) in Cipada through digital marketing training and the development of an integrated marketplace, desawisatacipada.com. Held on 19 May 2026 and involving 26 participants, the activity combined situational analysis, two training sessions on smartphone product photography and marketplace operation, hands-on assistance, and observation-based evaluation, and marked the soft launch of the marketplace. The results indicate that the training broadened participants' understanding of digital visual marketing and online selling. At the same time, the marketplace provides a shared economic space that supports the village's sustainable economic competitiveness.